Ab initio studies of the interaction potential for the Xe-NO(X2Π) van der Waals complex: bound states and fully quantum and quasi-classical scattering. - Kłos, J; Aoiz, F; Menéndez, M; Brouard, M; Chadwick, H; Eyles, C (2012)
Adiabatic potential energy surfaces for the ground electronic state of the Xe⋅⋅⋅NO(X(2)Π) van der Waals complex have been calculated using the spin-restricted coupled cluster method with single, double, and non-iterative triple excitations (RCCSD(T)). The scalar relativistic effects present in the Xe atom were included by an effective core potential and we extended the basis with bond functions to improve the description of the dispersion interaction. It has been found that the global minimum on the A(') adiabatic surface occurs at a T-shaped geometry with γ(e) = 94° and R(e) = 7.46 a(0), and with well depth of D(e) = 148.68 cm(-1). There is also an additional local minimum for the collinear geometry Xe-NO with a well depth of 104.5 cm(-1). The adiabat of A('') symmetry exhibits a single minimum at a distance R(e) = 7.68 a(0) and has a skewed geometry with γ(e) = 64° and a well depth of 148.23 cm(-1). Several C(nl) van der Waals dispersion coefficients are also estimated, of which C(6, 0) and C(6, 2) are in a reasonable agreement with previous theoretical results obtained by Nielson et al. [J. Chem. Phys. 64, 2055 (1976)]. The new potential energy surfaces were used to calculate bound states of the complex for total angular momentum quantum numbers up to J = 7/2. The ground state energy of Xe⋅⋅⋅NO(X(2)Π) is D(0) = 117 cm(-1), which matches the experimental value very accurately (within 3.3%). Scattering calculations of integral and differential cross sections have also been performed using fully quantum close coupling calculations and quasi-classical trajectory method at a collision energy of 63 meV. These calculations reveal the important role played by L-type rainbows in the scattering dynamics of the heavier Rg-NO(X) systems.